PENGARUH PROBLEM BASED LEARNING BERBANTUAN VIDEO PEMBELAJARAN DUAL MODALITY TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS VIII - Auliannisa Ichwan, Aghnia; Khaerunnisa, Etika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The mathematical critical thinking ability of junior high school students remains at a low to moderate level, particularly in geometry which requires high visualization skills. This study aims to determine whether the critical thinking ability of students using the Problem Based Learning (PBL) model assisted by dual modality learning video is better than students using PBL without video assistance. This study employed a quasi-experimental design with a nonequivalent control group design. The research subjects were eighth-grade students of SMP Negeri 29 Kota Bekasi, consisting of 34 students of class VIII F as the experimental group and 34 students of class VIII G as the control group. The instrument used was a critical thinking ability test in essay form consisting of 6 items with a maximum score of 24. Data analysis was conducted using the Independent Sample T-Test after the data met normality and homogeneity assumptions. The results showed that the mean posttest score of the experimental class was 16.29, higher than the control class at 14.94. The Independent Sample T-Test produced a Sig. (1-tailed) value of 0.0115, less than 0.05, thus H0 was rejected. The critical thinking ability of students using PBL assisted by dual modality learning video was proven to be better than students using PBL without video assistance on flat geometry material in eighth grade.